PTU-115 Identifying Nafld In Patients Attending A Lipid Clinic – Do Non-invasive Scoring Systems For Fibrosis Have A Role?. (9th June 2014) - Wong, L; Roberts, M; McCorry, R
Abstract : Introduction: Hyperlipidaemia is a recognised risk factor for the development of non-alcoholic fatty liver disease (NAFLD). Aspartate aminotransferase (AST):alanine aminotransferase (ALT) ratio, AST-to-Platelet Ratio Index (APRI) and Fibrosis-4 (FIB-4) scores are validated, indirect, non-invasive methods which can be employed to exclude the possibility of hepatic fibrosis in the context of NAFLD. 1 The aim of this study was to apply these indices to patients attending a lipid clinic, with an elevated ALT to determine what proportion would merit further hepatology assessment. Methods: We performed retrospective analysis of patients attending a lipid clinic in a university teaching hospital from 2011–2013. None of the patients were under gastroenterology/hepatology follow-up. In those with elevated ALT (>30 IU/L male, >19 IU/L female 2 ) we calculated the AST:ALT ratio, APRI and FIB-4 scores. Results: 130 patients were included (68 male, 62 female; mean age 54 (17–93)). Platelet data was available for 113 patients and 69 (53.0%) had elevated ALT (52% male). In these patients the scoring systems demonstrated an AST:ALT ratio >0.8 in 32 (46.4%), APRI >0.51 in 20 (30.0%) and FIB-4 >1.46 score in 14 (20.3%). 11 (15.9%) had high scores across all 3 indices. Conclusion: We have demonstrated that a significant proportion of patients with lipid abnormalities and raised ALT may be at risk of NAFLD with fibrosis. By using a composite of these scoring systems it may be possible to identify those who would benefit most from assessment in hepatology outpatients with staging of fibrosis. References: Stuart McPherson, Stephen F Stewart, Elsbeth Henderson, Alastair D Burt, Christopher P Day. Simple non-invasive fibrosis scoring systems can reliably exclude advanced fibrosis in patients withnon-alcoholic fatty liver disease. Gut 2010:59:1265–1269 Prati D, Taioli E, Zanella A, Della Torre E, Butelli S, Del Vecchio E, Vianello L, Zanuso F, Mozzi F, Milani S, Conte D, Colombo M, Sirchia G. Updated definitions of healthy ranges for serum alanine aminotransferase levels. Ann Intern Med 2002 Jul 2;137(1):1–10 Disclosure of Interest: None Declared.